2018
DOI: 10.1016/j.lfs.2018.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Acute exercise alters homocysteine plasma concentration in an intensity-dependent manner due increased methyl flux in liver of rats

Abstract: Our data provided evidence that acute exercise increases plasma Hcy concentration due to the augmented requirement for methylated compounds that increases liver SAM consumption. Also, Hcy remethylation and transsulfuration are coordinately regulated to maintain methyl balance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…The observed decrease in methionine and increase in tHcy post-exhaustive exercise may thus reflect increased transmethylation in which DNA, histones and other macromolecules are methylated in response to exercise. Indeed, one animal experiment showed that plasma methionine availability is an important determinant of intracellular methylation capacity (Mentch et al, 2015), and postexercise elevations in tHcy is thought to reflect increased methyl flux in tissues (Riberio et al, 2018). It has been reported that acute exercise induced immediate hypomethylation of several genes in skeletal muscle biopsies obtained from healthy individuals (Barres et al, 2012).…”
Section: Potential Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed decrease in methionine and increase in tHcy post-exhaustive exercise may thus reflect increased transmethylation in which DNA, histones and other macromolecules are methylated in response to exercise. Indeed, one animal experiment showed that plasma methionine availability is an important determinant of intracellular methylation capacity (Mentch et al, 2015), and postexercise elevations in tHcy is thought to reflect increased methyl flux in tissues (Riberio et al, 2018). It has been reported that acute exercise induced immediate hypomethylation of several genes in skeletal muscle biopsies obtained from healthy individuals (Barres et al, 2012).…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…Hypo-and hypertmethylation of DNA and histones are thought to be implicated in tissue response to acute and long-term exercise (Barres et al, 2012;Voisin et al, 2015;Seaborne et al, 2018;Hunter et al, 2019;Landen et al, 2019;Turner et al, 2019), and are dependent on availability of plasma and cellular methionine concentrations (Mentch et al, 2015). Tissue consumption of methionine for methylation reactions have been demonstrated in exercising mice (Riberio et al, 2018) and has been linked to observed post-exercise increases in plasma total homocysteine (tHcy) in humans (Deminice et al, 2016). In addition to being a potential marker of methylation reactions, elevated tHcy may impair endothelial nitric oxide synthesis (Stühlinger et al, 2001) with potential adverse effects on recovery and performance (Kingwell, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Dysfunction of liver alters methionine metabolism, resulting in elevated homocysteine that is released into the plasma. In return, homocysteine can in uence the status of liver as well (16). Our previous study proposed that ER stress might explain the pathogenic effects of homocysteine on liver injury, while its molecular mechanism remains obscure (17).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, compared to control, moderate exercise was much more e cient on decreasing DMGV than vigorous exercise with an equal effect on IHTG reduction, though vigorous exercise was more e cient on improvement of weight, waist circumference, body fat and visceral fat. It was con rmed that various exercise intensities impacted plasma metabolic pro le differently [18][19][20] , and low-intensity exercise favors a fat oxidation rate than in the high intensity exercise group with a greater decrease in body mass and fat mass 21 , thus, we considered that moderate exercise bene ts DMGV metabolism better than vigorous exercise might due to the better improvement on enzyme related to DMGV metabolism and oxidation ability, which needed further investigation.…”
Section: Discussionmentioning
confidence: 99%